2019
DOI: 10.1104/pp.18.01409
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Hydroxy-Triacylglycerol Is Efficiently Produced by Position-Specific Castor Acyltransferases

Abstract: J.B.).Understanding the biochemistry of triacylglycerol (TAG) assembly is critical in tailoring seed oils to produce high-value products. Hydroxy-fatty acid (HFA) is one such valuable modified fatty acid, which can be produced at low levels in Arabidopsis (Arabidopsis thaliana) seed through transgenic expression of the castor (Ricinus communis) hydroxylase. The resulting plants have low seed oil content and poor seedling establishment, indicating that Arabidopsis lacks efficient metabolic networks for biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 42 publications
3
47
0
2
Order By: Relevance
“…Similar phenomena have also been previously observed with transgene expression of FAD2, which produces unusual FAs, including epoxidation, hydroxylation and double bonding conjugation [40,41]. One hypothesis explaining this phenotype is that unusual FA products inhibit the activity of FAD2, thereby effectively preventing the conversion of C18:1 to C18:2 [43][44][45][46]. In The GhFAD2-1, GhFAD3, GhSAD, GhCYP704B1, GhCYP86B1, GhHTH, GhALDH, GhPXG, and GhCYP94C1 mRNA abundance was determined by qRT-PCR, respectively.…”
Section: A Role For Ghfad2-3 In Anther and Pollen Developmentsupporting
confidence: 78%
“…Similar phenomena have also been previously observed with transgene expression of FAD2, which produces unusual FAs, including epoxidation, hydroxylation and double bonding conjugation [40,41]. One hypothesis explaining this phenotype is that unusual FA products inhibit the activity of FAD2, thereby effectively preventing the conversion of C18:1 to C18:2 [43][44][45][46]. In The GhFAD2-1, GhFAD3, GhSAD, GhCYP704B1, GhCYP86B1, GhHTH, GhALDH, GhPXG, and GhCYP94C1 mRNA abundance was determined by qRT-PCR, respectively.…”
Section: A Role For Ghfad2-3 In Anther and Pollen Developmentsupporting
confidence: 78%
“…A recent study reported that coexpression of three castor acyltransferase enzymes in the Kennedy pathway produced 19% TAG3 and concentrated 44% of seed HFA moieties into this one TAG species. RA was more abundant than any other fatty acid in these seeds, which had three-fold more HFA by weight than that in seeds following simple hydroxylase expression (Lunn et al, 2019). It may be explained that RcPLD9 co-evolved with other essential genes in the lipid metabolic pathway of castor bean, especially genes using effective RA-CoA for TAG synthesis in the Kennedy pathway such as DGAT, LPAAT, and GPAT.…”
Section: Discussionmentioning
confidence: 97%
“…In the past decade, many genes responsible for RA synthesis and its accumulation in castor bean have been identified by functionally characterizing them in the model plant Arabidopsis due to the lack of efficient castor transformation methods (Aryal and Lu, 2018;Bayon et al, 2015;Burgal et al, 2008;Chen et al, 2016;Hu et al, 2012;Kim et al, 2011;Lu et al, 2006;Lunn et al, 2019;Smith et al, 2003;van de Loo et al, 1995;van Erp et al, 2011). Fatty acid hydroxylase 12 (FAH12) catalyzes RA production by hydroxylating oleic acid (18:1n-9) at the sn-2 position of phosphatidylcholine (PtdCho) (Bafor et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis explaining this phenotype is that unusual FA products inhibit the activity of FAD2, thereby effectively preventing the conversion of C18:1 to C18:2 [43,45,46]. In cottonseed, the relative content of C18:2 peaked in the mature seeds, accounting for over 50% of the total fatty acid content of seed [12].…”
Section: A Role For Ghfad2-3 In Anther and Pollen Developmentmentioning
confidence: 99%